PREFERENSI KONSUMEN IKAN CAKALANG DI KELURAHAN SODOHOA KECAMATAN KENDARI BARAT KOTA KENDARI - Rikal Ma'ruf; B. Budiyanto; Akhmad Mansyur (UNIVERSITAS HALU OLEO, 2022)
This study aims to determine consumer preferences forskipjack tuna consumers in Sodohoa Village, West Kendari District, Kendari City in January 2022. The method used is accidentasl sampling. The number of samples is this study was 30 samppes. The variables observed were fish size, price, color, cleanliness, and texture of skipjack tuna. Analysis of the data used is Conjoint Analysis. The results showed that the preferences of consumers namely skipjack tuna which is cheap, brightly colored, stiff textured, clean, with a size of 1 fish/3 kg. Keywords: Conjoint Analysis; Skipjack Tuna; Consumer Preference